Housing for the poor in a neo‐liberalising just city: Still affordable, but increasingly inaccessible. (10th November 2014) - Kadi, Justin; Musterd, Sako
Abstract With a comparably high degree of de‐commodification in the urban housing market, Amsterdam has been long considered a prime example of a 'European city' and a 'just city'. This paper looks at how the city's housing tenure sectors have changed since the 1990s due to neo‐liberalisation processes and specifies effects for housing conditions of the poor. It highlights how restructuring has been driven by policy changes at different scales, and analyses the effects of reform on issues of accessibility and affordability. We identify a gap between insiders and outsiders, with affordability for the poor inside the system not yet deteriorating, but accessibility for poor outsiders emerging as a key problem. In the conclusion we speculate on future developments of the Amsterdam housing market and relate our findings to debates about the 'European city' and the 'just city'.